Analisis Pemanfaatan Pinjaman Dana Bergulir Program Kota Tanpa Kumuh di Kecamatan Gayungan Kota Surabaya - Ika Oktaviyanti; Dhani Nur Ichsanuddin (JDEP (Jurnal Dinamika Ekonomi Pembangunan), 2020)
This research is a quantitative study with data collection techniques using a questionnaire. The population used was all members of the self help group in Gayungan District, Surabaya City as many as 95 people. This study uses a sample with the census method. The census sample is the determination of the sample if all members of the population are used as the sample (Sugiyono, 2012). The data processing technique uses Partial Least Square (PLS) analysis, Outer Model, Inner Model, and Hypothesis Testing. The results of this study concluded: 1)Financial Literacy can contribute to the Utilization of Revolving Fund Loans; 2) Financial Experience can contribute to the Utilization of Revolving Fund Loans; 3) Income can contribute to the Utilization of Revolving Fund Loans; 4) Attitude of Managers Finance as a moderation of the Financial Literacy variable cannot contribute to the Utilization of Revolving Loans; 5) The attitude of the Financial Managers as a moderation of the Financial Experience variable cannot contribute to the Utilization of Revolving Loans; dan 6) The attitude of the Financial Manager as a moderation of the Income variable doesn’t contribute on the Utilization of Revolving Loans.